2014
DOI: 10.1007/s11284-014-1154-1
|View full text |Cite
|
Sign up to set email alerts
|

Are tropical butterflies more colorful?

Abstract: There is a common and long‐standing belief that tropical butterflies are more striking in their coloration than those of cooler climates. It has been suggested that this is due to more intense biotic selection or mate selection in the tropics. We tested whether there were differences in coloration by examining the dorsal surface color properties of male butterflies from three regions of the western hemisphere: the Jatun‐Satcha Reserve in lowland Ecuador (tropical), the state of Florida, USA (subtropical) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…In our tropical sites, models of different colors were generally attacked at similar rates (except for the brightest, most attacked, white models), which may be explained by a decreased ability of birds to discriminate colors in the understory of tropical forest due to low light intensity (Gomez et al, ; Olsson, Lind, & Kelber, ). Similar attack frequencies on prey of different colors in our tropical sites might also be attributable, in part, to a higher variability in coloration of insects in the tropics, as demonstrated, for example, for butterflies (Adams et al, ). Birds in tropical forests are therefore faced with a higher variety of prey colors than birds in temperate and boreal forests, where models of some colors can be rejected by birds due to neophobia, that is, the avoidance of an object solely because it has never been experienced (Greenberg & Mettke‐Hofman, ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our tropical sites, models of different colors were generally attacked at similar rates (except for the brightest, most attacked, white models), which may be explained by a decreased ability of birds to discriminate colors in the understory of tropical forest due to low light intensity (Gomez et al, ; Olsson, Lind, & Kelber, ). Similar attack frequencies on prey of different colors in our tropical sites might also be attributable, in part, to a higher variability in coloration of insects in the tropics, as demonstrated, for example, for butterflies (Adams et al, ). Birds in tropical forests are therefore faced with a higher variety of prey colors than birds in temperate and boreal forests, where models of some colors can be rejected by birds due to neophobia, that is, the avoidance of an object solely because it has never been experienced (Greenberg & Mettke‐Hofman, ).…”
Section: Discussionsupporting
confidence: 70%
“…Bird responses to prey that differ in appearance, including coloration, are influenced by previous experience (Ruxton et al, ). The experience of birds in a certain habitat depends on the composition of the local prey community, and particularly on the variability in coloration of local prey species, which may differ between tropical and temperate sites (Adams, Kang, & June‐Wells, ). Great environmental variability was found to reduce the avoidance of novel foods by birds (Greenberg & Mettke‐Hofman, , and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, much of the theoretical footing for the colorful‐tropics hypothesis rested on arguments of higher diversity in tropical ecosystems selecting for more flamboyant and conspicuous color signals (Adams et al. ). However, we have here shown that many components of the abiotic environment are as important (or more important) than the diversity of the wider biotic community in affecting bird and butterfly coloration overall.…”
Section: Discussionmentioning
confidence: 99%
“…On exploring tropical Venezuela, Humboldt noted the ‘bright‐red flowers’ and the ‘colours in birds, fish, even crayfish (sky blue and yellow)!’ (von Humboldt, , p. 6). Fascinated by seemingly stark differences between tropical regions of the world and those further away from the equator, biologists have repeatedly attempted to delineate colour dissimilarities across latitudes (Darwin, ; Wallace, , , ; Poulton, ; Weevers, ; Wilson & von Neumann, ; Bailey, ; Adams et al ., ). Differences in colouration have been taken for granted by many tropical biologists or ecologists.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Wilson and von Neumann () concluded that the inhabitants of tropical South America were the most colourful of the Pan‐American avifauna, and Adams et al . () concluded that butterflies (excluding the diverse, yet dull‐coloured Hesperiids) in tropical Ecuador are more colourful than those in subtropical and temperate regions of North America. However, conclusions from these studies are limited, first due to their focus on single taxonomic groups, but second, and more seriously, because of their reliance on human‐based assessment of coloration.…”
Section: Introductionmentioning
confidence: 99%